2018
DOI: 10.5152/turkpediatriars.2018.5389
|View full text |Cite
|
Sign up to set email alerts
|

The follow-up results of newborn hearing screening of Gaziosmanpasa Taksim Research and Training Hospital

Abstract: Bu çalışmayla hastanemizden yenidoğan işitme taraması sonucu ileri işitme merkezlerine sevk edilen yenidoğanların işitme kaybı tanı yaşı, işitme cihazı takılma süresi ve kohlear implantasyon zamanının Amerikan Pediatri Akademisi tanı ve tedavi hedefleri ile uyumunun araştırılması hedeflendi. Gereç ve Yöntemler: Bu çalışmaya Mart 2014-Haziran 2016 tarihleri arasında Gaziosmanpaşa Taksim Eğitim Araştırma Hastanesi'nde işitme taraması yapılan 7 502 bebek alındı. Bebeklerin işitme taramasında ilk iki basamakta uya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…The present study findings indicated a significant trend towards earlier identification of HL, amplification and initiation of education across the years after implementation of NHSP. This finding was consistent with previous studies (Al-Sayed & Al-Sanosi, 2017;Aras-Öztürk et al, 2018;Bruijnzeel et al, 2017;Wasser, Roth, Herzberg, Lerner-Geva & Rubin, 2019). Comparison of the year periods demonstrated significant decreases in the whole group, GR1 and GR2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study findings indicated a significant trend towards earlier identification of HL, amplification and initiation of education across the years after implementation of NHSP. This finding was consistent with previous studies (Al-Sayed & Al-Sanosi, 2017;Aras-Öztürk et al, 2018;Bruijnzeel et al, 2017;Wasser, Roth, Herzberg, Lerner-Geva & Rubin, 2019). Comparison of the year periods demonstrated significant decreases in the whole group, GR1 and GR2.…”
Section: Discussionsupporting
confidence: 93%
“…Although the decrease was significant, the mean ages in all categories were still above the standards recommended by JCIH (2007). These findings were consistent with other studies conducted in Turkey (Aras-Öztürk et al, 2018;Konukseven et al, 2017;Yılmazer et al, 2016) and some other countries (Holte et al, 2012;Jeddi et al, 2012;Kasai et al, 2012;Saki et al, 2018;Wasser et al, 2019). The time gap between the diagnosis and initiation of education almost seven months in GR1 even during the 2010-2017 period, where long term results were expected.…”
Section: Discussionsupporting
confidence: 92%